Neuroinflammation and Lysosomal Abnormalities Characterise the Essential Role for Oxidation Resistance 1 in the Developing and Adult Cerebellum - Eboni M. V. Bucknor; Errin Johnson; Stephanie Efthymiou; Javeria R. Alvi; Tipu Sultan; Henry Houlden; Reza Maroofian; Ehsan G. Karimiani; Mattéa J. Finelli; Peter L. Oliver (MDPI AG, 2024)
Loss-of-function mutations in the TLDc family of proteins cause a range of severe childhood-onset neurological disorders with common clinical features that include cerebellar neurodegeneration, ataxia and epilepsy. Of these proteins, oxidation resistance 1 (OXR1) has been implicated in multiple cellular pathways related to antioxidant function, transcriptional regulation and cellular survival; yet how this relates to the specific neuropathological features in disease remains unclear. Here, we investigate a range of loss-of-function mouse model systems and reveal that constitutive deletion of Oxr1 leads to a rapid and striking neuroinflammatory response prior to neurodegeneration that is associated with lysosomal pathology. We go on to show that neuroinflammation and cell death in Oxr1 knockouts can be completely rescued by the neuronal expression of Oxr1, suggesting that the phenotype is driven by the cell-intrinsic defects of neuronal cells lacking the gene. Next, we generate a ubiquitous, adult inducible knockout of Oxr1 that surprisingly displays rapid-onset ataxia and cerebellar neurodegeneration, establishing for the first time that the distinctive pathology associated with the loss of Oxr1 occurs irrespective of developmental stage. Finally, we describe two new homozygous human pathogenic variants in OXR1 that cause neurodevelopmental delay, including a novel stop-gain mutation. We also compare functionally two missense human pathogenic mutations in OXR1, including one newly described here, that cause different clinical phenotypes but demonstrate partially retained neuroprotective activity against oxidative stress. Together, these data highlight the essential role of Oxr1 in modulating neuroinflammatory and lysosomal pathways in the mammalian brain and support the hypothesis that OXR1 protein dosage may be critical for pathological outcomes in disease.